Applying Andersen's healthcare utilization model to assess factors influencing patients' expectations for diagnostic tests at emergency department visits during the COVID-19 pandemic - Huang, Zhilian; Natarajan, Karthiga; Lim, Hoon Chin; Weng, Yanyi; Tan, Hann Yee; Seow, Eillyne; Peng, Li Lee; Ow, Jing Teng; Kuan, Win Sen; Chow, Angela (Frontiers in Public Health, 2023)
The uncertainties surrounding the COVID-19 pandemic led to a surge in non-urgent emergency department (ED) attendance among people presenting with upper respiratory tract infection (URTI) symptoms. These non-urgent visits, often manageable in primary care, exacerbated ED overcrowding. Understanding patients’ expectations and the reasons for these ED visits is imperative to mitigate the problem of ED overcrowding. Hence, we assessed the factors influencing patients’ expectations for diagnostic tests during their ED visits for uncomplicated URTI during different phases of the pandemic. We conducted a cross-sectional study on adults with URTI symptoms seeking care at four public EDs in Singapore between March 2021 and March 2022. We segmented the study period into three COVID-19 pandemic phases— Containment, Transition, and Mitigation. The outcome variables are whether: patients expected 1) a COVID-19-specific diagnostic test, 2) a non-COVID-19-specific diagnostic test, 3) both COVID-19-specific and non-COVID-19-specific diagnostic tests, or 4) no diagnostic test. We built a multinomial regression model and classified the findings according to Andersen’s healthcare utilisation model. The mean age of participants was 34.5 (12.7) years. Factors (adjusted odds ratio [95% confidence interval]) influencing expectations for a COVID-19-specific diagnostic test in the ED include younger age (21–40 years: (2.98[1.04–8.55]), no prior clinical consultation (2.10[1.13–3.89]), adherence to employer’s health policy (3.70[1.79–7.67]), perceived non-severity of illness (2.50[1.39–4.55]), worry about contracting COVID-19 (2.29[1.11–4.69]), and during the transition phase of the pandemic (2.29[1.15–4.56]). Being non-employed influenced the expectation for non-COVID-19-specific diagnostic tests (3.83[1.26–11.66]). Factors influencing expectations for both COVID-19-specific and non-COVID-19-specific tests include younger age (21–40 years:(3.61[1.26–10.38]); 41–60 years:(4.49[1.43–14.13])), adherence to employer’s health policy (2.94[1.41–6.14]), worry about contracting COVID-19 (2.95[1.45– 5.99]), and during the transition (2.03[1.02–4.06]) and mitigation (2.02[1.03–3.97]) phases of the pandemic. Patients’ expectations for diagnostic tests during ED visits for uncomplicated URTI were dynamic across the COVID-19 pandemic phases. Expectations for COVID-19-specific diagnostic tests for ED visits for uncomplicated URTI were higher among younger individuals and those worried about contracting COVID-19 during the COVID-19 pandemic. Future work is required to enhance public communications on the availability of diagnostic services in primary care and public education on self-management of emerging infectious diseases such as COVID-19.